Pemberdayaan Masyarakat Pesisir Dalam Kajian Participation Action Research Di Desa Beras Basah - Rahmadani, Suci; Herlina, Sri; Asmayani, Asmayani; Angriani, Weny Lovia; Lubis, Lewis Pramana; Barus, Dana Syahputra (Yayasan Kawanad, 2025)
This study aims to analyze the community empowerment model implemented in Beras Basah Village, North Sumatra, focusing on active citizen participation as the core of development. The research employed a qualitative descriptive approach through the Participatory Action Research (PAR) model. Data were collected through interviews, focus group discussions, and field observations involving local officials, fishermen’s groups, and coastal women. The findings indicate that the success of empowerment initiatives largely depends on collaboration among local government, the community, and academia. Collective commitment to environmental preservation, participatory leadership, and the establishment of locally based institutions emerged as key factors sustaining the program’s continuity. Beyond improving income, empowerment has fostered social solidarity, collective responsibility, and critical awareness regarding sustainable resource management. Thus, community empowerment in Beras Basah Village not only enhances economic resilience but also strengthens social foundations rooted in adaptability and democratic values